The Joined-up Magnetosphere - Lockwood, Mike (Frontiers in Astronomy and Space Sciences, 2022)
Systems science is a relatively new way of studying the magnetosphere. This perspective outlines the need for it and how it can contribute to our understanding and so give more reliable forecasts, predictions, and space weather climatologies.